Sharing housework between husbands and wives: How to improve marital satisfaction for working wives in Japan - Mayu Kobayashi; Miki Kobayashi; Tsunao Okumura; Emiko Usui (IZA Journal of Labor Policy, 2016)
This paper examines whether and how the marital satisfaction of Japanese couples is related to the housework the spouse performs. For single-earner couples, both husbands and wives are more satisfied with the other spouse if the wife performs the greater share of the housework on weekdays. In dual-earner couples, both husbands and wives experience higher spousal satisfaction when the other spouse performs more housework on weekdays. Japanese dual-earner couples are unable to spend more time on housework, because wives are already performing a significant share of housework on weekdays while husbands are working long hours.
Keywords: J12; J22; 330; Marriage; Housework/division of labor; Satisfaction; Time use; Wives' employment